Tactical behavior in soccer small-sided games: inluence of team composition criteria - Gibson Moreira Praça; Juan Carlos Pérez Morales; Pedro Emílio Drumond Moreira; Gustavo Henrique Cunha Peixoto; Sarah Teles Bredt; Mauro Heleno Chagas; Israel Teoldo; Pablo Juan Greco (Universidade Federal de Santa Catarina, 2017)
This study aimed to compare the tactical behavior of young soccer players during small-sided games played with team composition criteria based on procedural tactical knowledge, aerobic power and speed performance. Eighteen male soccer players played 3vs.3 small-sided games with teams balanced according to players' performance on Sprint Test, Yo-Yo Intermittent Recovery Test and the ield test of the System of Tactical Assessment in Soccer. Data related to the incidence of tactical principles were analyzed through the proportions chi-square test with Bonferroni's correction. One-way ANOVA was used to compare players' ofensive and defensive tactical performance. Results showed diferent incidence of ofensive and defensive tactical principles in games with diferent teams' composition criteria. It has also been shown a higher defensive performance when the teams' composition criteria was based on players' procedural tactical knowledge.